Implementasi Kurikulum Merdeka Dan Ketersediaan Sumber Belajar Pada Mata Pelajaran Akidah Akhlak di MTs Negeri 2 Wonosobo - Setya Dwi Aryati; Mukromin Mukromin; Faisal Kamal (Institut Nalanda, 2024)
To collect data in the field, the thesis uses a qualitative descriptive field study methodology. An observation approach, interviews with various sources including the deputy head of curriculum, Aqidah akhlaq teacher, and MTs Negeri 2 Wonosobo students were used as data collection strategies. Documentation in the form of pictures of the interview process, school profiles and learning activities is also used. Research findings show that although the introduction of an autonomous curriculum and provision of resources for learning about moral beliefs at MTs Negeri 2 Wonosobo has gone quite well, there is still room for improvement because various stakeholders are still getting used to the new curriculum. arrangement. Naturally, the teacher has prepared himself and the lesson is carried out before it begins, and the materials for gaining moral conviction are available. Infrastructure, facilities and the presence of teachers who always strive to become better qualified are variables that support the implementation of moral learning based on an independent curriculum. Meanwhile, the obstacle is that teachers' understanding of the independent curriculum policy is still lacking because of course it requires preparation time during the curriculum transition period. Additionally, there is a lack of understanding of how schools and teachers can update and enhance new content in independent curricula and how to build strong teams for project modules.